How PC is your PC? [personal computer lifespan]. - Predd, P.P.
This paper discusses the report by Eric Williams on the fact that the personal computer is not energy efficient and environmentally friendly. The analysis was based on a PC with a Pentium III processor and a 17-inch cathode ray tube screen. Detailed assessment was made to calculate the total energy and materials that go into manufacturing a PC and have shown that it is actually a highly energy-intensive process. Taking into account the PC's rather short average lifespan of about three years, the computer's average annual energy cost is greater than that of household appliances such as refrigerators which last at about 15 years.
Keywords: PC manufacture; Energy cost; Energy efficiency; Energy-intensive process; Environmental friendliness; Personal computer lifespan